2012
DOI: 10.1371/journal.pone.0043514
|View full text |Cite
|
Sign up to set email alerts
|

The Human Milk Protein-Lipid Complex HAMLET Sensitizes Bacterial Pathogens to Traditional Antimicrobial Agents

Abstract: The fight against antibiotic resistance is one of the most significant challenges to public health of our time. The inevitable development of resistance following the introduction of novel antibiotics has led to an urgent need for the development of new antibacterial drugs with new mechanisms of action that are not susceptible to existing resistance mechanisms. One such compound is HAMLET, a natural complex from human milk that kills Streptococcus pneumoniae (the pneumococcus) using a mechanism different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 72 publications
2
59
0
Order By: Relevance
“…Of particular interest are potentiators of existing antibiotics, or codrugs, a number of which have been used in both laboratory (18)(19)(20)(21)(22)(23) and clinical (24)(25)(26) settings. Also, Collins and coworkers have demonstrated that specific metabolites can potentiate aminoglycosides acting on E. coli and Staphylococcus aureus biofilms (27).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are potentiators of existing antibiotics, or codrugs, a number of which have been used in both laboratory (18)(19)(20)(21)(22)(23) and clinical (24)(25)(26) settings. Also, Collins and coworkers have demonstrated that specific metabolites can potentiate aminoglycosides acting on E. coli and Staphylococcus aureus biofilms (27).…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of antibiotics in liprotides has the potential to be exploited in a similar way. The synergetic effect of using antibiotics together with HAMLET is already known (32) , but might be further exploited if the antibiotics could be incorporated in the liprotide structure thereby potentially increasing the solubility, stability and transport of the antibiotic to a target cells. However, the antibiotics investigated in this study were not able to form a complex with aLA and OA, highlighting that not all small molecules are able to bind to liprotides.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then resuspended in fresh PBS. SEM determinations were performed as described before (47,48). Briefly, 10 l of cell suspensions was settled on poly-L-lysine-coated round coverslips (BD BioSciences, San Jose, CA).…”
Section: Fig 1 Construction Of the Rrp1mentioning
confidence: 99%